Call him Mac : Ernest W. McFarland, the Arizona years - Stuart, Gary L., 1939- (Sentinel Peak, an imprint of The University of Arizona Press, 2018)
"The story behind Arizona governor, Supreme Court justice, and legend Ernest 'Mac' McFarland"--Provided by publisher